ANALISIS DAN OPTIMASI SIMPANG BERSINYAL SEMI KOORDINASI DENGAN MENGGUNAKAN SYNCHRO 7.0 - Aan Setiawan; Chesty Asriningtyas; Ismiyati Ismiyati; Kami Hari Basuki (Jurnal Karya Teknik Sipil, 2014)
The change of used areas in Siliwangi road, from settlement to be the centre of business – service, industrials and office, will appear traffic movement in Krapyak and Tol Krapyak – Jatingaleh intersection. Moreover there will be some problem on traffic phenomena as traffic jam, time of delay, air pollution that increase, accident and other traffic problem that will cause lose time, fuel use, and cost. This study aims to analyzed the performance of Krapyak intersection and Tol Krapyak – Jatingaleh intersection, it should be changed the traffic management and geometric research to minimized the traffic jam and air pollution on both intersection. The pattern of the movement of the road beside both intersection can be obtained by using origin – destination matrix (ODM). The advantage of this method in which the vehicle volume and the value of obstacle in each intersection, the pattern traffic movement can be gained. Of course it will minimized the cost, time, human resources. The performance of the intersection will be measure and analyzed using Synchro 7.0 from America. The advantage of this program is able to stimulate planning yield and easy to operate as well. The alternated solution from this study is to broaden road lines of 3,5 meter on each intersection and the alternated road for vehicle to public transportation in the value of 40%. The result of this analyzed in existing condition is measured by DS value on Krapyak intersection 1,29; emission of CO 2089 gram and in Tol Krapyak – Jatingaleh is of 1,41; emission CO 1903 gram. The broaden of road line (3,5 meter) the value DS Krapyak intersection 0,73 (decrease 43,3%); emission CO 2293 gram (increase 8,89%) in Tol Krapyak – Jatingaleh intersection the value DS 0,74 (decrease 47,5%); emission CO 1899 gram (decrease 0,21%). The assumption of the change of private to public transportation of 40% the value DS in Krapyak intersection 0,71% (decrease 44,9%); emission CO 1353 gram (decrease 35,2%) in Tol Krapyak – Jatingaleh intersection the value DS 0,62% (decrease 56%); emission CO 1120 gram (decrease 41,1%). The result of analysis can be concluded, assumption transfer of private car to public transportation equal to 40% is solution able to be optimal of performance service of intersection. Where result of DS equal to 0,71 and 0,62 which have fulfilled conditions of intersection performance ≤ 0,75, and also emission of CO 1,353 ppm and 1,120 ppm have fulfilled conditions of value float pollution boundary that is, ranging from 0 - 50 ppm where, entering in good category (there no effect to environment and health). Hence can be recommended, for related government utilize to repair the pre requirement and suitable requirement public transportations, and improve security, service of consumer of public transportation. In research hereinafter, enabled to use ODM method and program of Synchro 7.0.